Married men's sexual and reproductive health concerns and related health-seeking behavior in Bangladesh: A mixed methods study - Raia Azmi; Ilias Mahmud; Kuhel Faizul Islam; Md Tanvir Hasan; Sabina Faiz Rashid (BMC, 2022)
Abstract Background In Bangladesh, men's sexual and reproductive health (SRH) needs and related services are often neglected. Little is known of men's SRH concerns, and of the phenomenal growth of the informal and private health actors in the provision of sexual health services to men in rural and urban areas of Bangladesh. Methods Using a mixed methods approach, a survey of 311 married men in three rural and urban sites was conducted in three different districts of Bangladesh and 60 in-depth interviews were conducted to understand their SRH concerns and choice of providers to seek treatment. Results The research findings reveal that- men's various SRH concerns are embedded in psychosocial and cultural concerns about their masculinity and expectations of themselves as sexual beings, with worries about performance, loss of semen and virility being dominant concerns. Sexually transmitted infections (STIs) were also mentioned as a concern but ranked much lower. Informal providers such as village doctors (rural medical practitioners and palli chikitsoks), drug store salespeople, homeopaths, traditional healers (Ojha/pir/fakir, kabiraj, totka) and street sellers of medicines are popular, accessible and dominate the supply chain. Conclusion There is a need of appropriate interventions to address men's anxieties and worries about their sexual abilities, well-being and choice of providers. This would go a long way to address and alleviate concerns, as well as identify and push men to seek  formal care for asymptomatic STIs, and thereby reduce costs incurred and gender tensions in households.